2008
DOI: 10.1007/978-1-60327-517-0_22
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Biotransformed Sex Hormones Facilitated by Bacillus stearothermophilus

Abstract: Bacillus stearothermophilus, a thermophilic bacterium isolated from Kuwaiti desert, when incubated with exogenous progesterone for 10 days at 65 degrees C produced two monohydroxylated, two dihydroxy isomers of progesterone and a B-Seco compound. These metabolites were purified by TLC and HPLC followed by their identification through (1)H, (13)C NMR and other spectroscopic data. Microbial hydroxylation of 17beta-estradiol resulted in the production of estrone. The effect of some inducers resulted in the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…6α-Hydroxyprogesterone is another natural occurring metabolite which is produced during the metabolism of progesterone, especially by fetal liver and placental enzymes during pregnancy (Lisboa and Gustafsson 1969). In the study of Afzal et al (2010), it was found that progesterone transformation products including 20α-, 6α-, and 6β-hydroxyprogesterone exhibit antioxidant activity more than progesterone alone. 6β-Hydroxylation has been reported by the isolated cytochrome P-450 enzyme and various Bacillus thermoglucosidasius (Sideso et al 1998;Wang et al 2000).…”
Section: Resultsmentioning
confidence: 98%
“…6α-Hydroxyprogesterone is another natural occurring metabolite which is produced during the metabolism of progesterone, especially by fetal liver and placental enzymes during pregnancy (Lisboa and Gustafsson 1969). In the study of Afzal et al (2010), it was found that progesterone transformation products including 20α-, 6α-, and 6β-hydroxyprogesterone exhibit antioxidant activity more than progesterone alone. 6β-Hydroxylation has been reported by the isolated cytochrome P-450 enzyme and various Bacillus thermoglucosidasius (Sideso et al 1998;Wang et al 2000).…”
Section: Resultsmentioning
confidence: 98%
“…Synthetic alterations of estrone lead to discovering of compounds with diverse biological activities, for example with antitumor effect [1], as anti-breast cancer agent [2] and with antioxidant activity [3]. Estrone derivatives with antitumor activities must be devoid completely of the estrogenic activities [4,5,6].…”
Section: Introductionmentioning
confidence: 99%